Eksistensi Bahasa Arab Amiyyah di Komunitas Keturunan Arab Indonesia - Chika Salsabila; Muhammad Azhar (Journal of Practice Learning and Educational Development, 2026)
Sociolinguistic studies view language not only as a means of communication but also as a representation of a community’s social and cultural identity. In multilingual societies, minority languages frequently face pressure from majority languages that dominate social, educational, and public communication domains. This study aims to describe the existence of Arabic Amiyyah within Indonesian Arab-descendant communities, analyze the social contexts of its use, and identify the supporting and inhibiting factors affecting its continuity within non-Arab-descendant societies. This research employed a qualitative method with a case study approach. Data was collected through interviews with informants who still use Arabic Amiyyah within family and community settings and were subsequently analyzed using descriptive qualitative techniques. The findings reveal that Arabic Amiyyah continues to exist, although its use is limited and contextual, particularly within family domains and internal community interactions with specific vocabulary, code-mixing, code-switching, and full utterances in certain situations. The existence of this language is supported by the role of the family, the presence of community networks, and cultural awareness as markers of Arab-descendant identity. However, the dominance of the Indonesian language, limited environments for language use, and declining interest among younger generations constitute the main factors hindering its continuity. This study contributes to the expansion of sociolinguistic research on the existence and maintenance of non-regional minority languages in Indonesia.